Show da Fé: espetáculo e televisibilidade na Igreja Internacional da Graça de Deus - Santos, Antônio (2020)
This research aims to analyze the practices adopted by the International Church of God's Grace in the television show "Show of Faith" as a strategy of attracting believers.This emerged in 2003 with the purpose of disseminating, through social media, especially on television, a differentiated religious programming to Brazil and foreign countries as well. Here one seeks to know its emergence, nature, techniques used and the symbolic goods of salvation presented in the program.The International Church of God's Grace, commonly called the Church of Grace, is a dissent from the Universal Church of the Kingdom of God, of neopentecostal origin, founded by Romildo Ribeiro Soares known as missionary R. R. Soares.The research is based on the premise that transformations in the Brazilian religious field favored the emergence of this new neopentecostal movement, which was born supported by prosperity theology and has been using the media and the mass media, especially television, as a tool for attracting the faithful. Accordingly, this work seeks to investigate the characteristics of this religious phenomenon and its adaptation to the components of the media industry. In addition, it is investigated how the Show of Faith, as a media-influenced religious spectacle, is restructured according to the logic of the media industry. It is also sought to investigate the symbolic goods offered in the aforementioned program, mainly from the religious work adopted by missionary R. R. Soares. It starts from the idea that missionary R. R. Soares adheres to the logic of the media industry as a way of maintaining his religious enterprise in the disputed market of symbolic goods of salvation. It also intends to make a relationship of how the figure of missionary R.R. Soares is related to the notion of television skill, as well as his charism within the television show. Finally, the research that is now underway proposes that the Missionary adheres to the logic of the media industry and uses symbolic goods on the television program "Show of faith" structured in religious work to attract believers.